Combining mutations that modulate inter-subunit interactions and proteolytic inactivation enhance the stability of factor VIIIa - Wakabayashi, Hironao; Wintermute, Jennifer M.; Fay, Philip J. (Thrombosis and Haemostasis, 2014)
FVIIIa is labile due to the dissociation of A2 subunit. Previously, we introduced hydrophobic mutations at select A1/A2/A3 subunit interfaces yielding more stable FVIII(a) variants. Separately we showed that altering the sequence flanking the primary FXa cleavage site in FVIIIa (Arg336) yielded reduced rates of proteolytic inactivation of FVIIIa. In this study we prepared the FXa-cleavage resistant mutant (336(P4-P3’)562) combined with mutations of Ala108Ile, Asp519Val/ Glu665Val or Ala108Ile/Asp519Val/Glu665Val and examined the effects of these combinations relative to FVIII thermal stability, rates of FVIIIa decay and proteolytic inactivation of FVIIIa by FXa. Thermal decay rates for 336(P4-P3’)562/Ala108Ile, 336(P4-P3’)562/Asp519Val/ Glu665Val, and 336(P4-P3’)562/Ala108Ile/Asp519Val/Glu665Val variants were reduced by ∼2– to 5-fold as compared with wild-type (WT) primarily reflecting the effects of the A domain interface mutations. FVIIIa decay rates for 336(P4-P3’)562/Asp519Val/Glu665Val and 336(P4-P3’)562/Ala108Ile/Asp519Val/Glu665Val variants were reduced by ∼25 fold, indicating greater stability than the control Asp519Val/Glu665Val variant (∼14-fold). Interestingly, 336(P4-P3’)562/Asp519Val/Glu665Val and 336(P4-P3’)562/Ala108Ile/ Asp519Val/Glu665Val variants showed reduced FXa-inactivation rates compared with the 336(P4-P3’)562 control (∼4-fold), suggesting A2 subunit destabilisation is a component of proteolytic inactivation. Thrombin generation assays using the combination variants were similar to the Asp519Val/Glu665Val control. These results indicate that combining multiple gain-of-function FVIII mutations yields FVIII variants with increased stability relative to a single type of mutation.
Keywords: Factor VIII; factor VIIIa; factor Xa; protein stability; thrombin generation assay